SIDIK SIAMA: An instrument for Risk Detection of Stunting Since Pregnancy - Devita Madiuw; Feby Manuhutu; Adriana Sainafat; Zasendy Rehena; Vanny Leutualy; Fandro Armando Tasijawa; Valensya Yeslin Tomasoa; Dian Thiofany Sopacua; Joan Herly Herwawan; Arthur Huwae (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Stunting problems need to be detected early so that the interventions given can reduce long-term effects. One of the reasonable periods to detect the risk of stunting is pregnancy. Ironically, there has not been an instrument to detect the risk of stunting since pregnancy. This study aims to develop and test the validity of an instrument for early detection of stunting risk since pregnancy (SIDIK SIAMA). Instrument development uses the seven stages of development from Roberth DeVellis (2017). A total of 20 women were involved in pre-testing, and 100 pregnant women were involved in instrument testing. Based on a literature search, 28 articles were used to construct the item pool and produce 10 items to be tested for validity and reliability. Content validity uses the content validity index (CVI) and construct validity used principal component analysis (PCA). Alpha Cronbach is used to test the reliability of the instrument. The validity test results showed that there were 9 valid and reliable items, with a CVI of 1 and a Measure of Sampling Adequacy (MSA) value of less than 0.5, and a Cronbach Alpha value of 0.682. Thus, the SIAMA SIDIK instrument has achieved good validity and reliability so that it can be used to detect the risk of stunting since pregnancy. Abstrak: Permasalahan stunting perlu dideteksi sejak dini, sehingga intervensi yang diberikan dapat mengurangi efek jangka panjang. Salah satu periode tepat untuk mendeteksi risiko stunting yaitu sejak kehamilan, ironisnya belum teridentifikasi instrumen untuk mendeteksi risiko stunting sejak masa kehamilan. Penelitian ini bertujuan untuk mengembangkan dan menguji validitas instrumen deteksi dini risiko stunting sejak kehamilan (SIDIK SIAMA). Pengembangan instrumen menggunakan tujuh tahapan pengembangan dari Roberth DeVellis (2017). Sebanyak 20 wanita terlibat dalam pre-testing dan 100 wanita hamil terlibat dalam pengujian instrumen. Berdasarkan pencarian literatur, 28 artikel digunakan untuk menyusun item pool dan menghasilkan 10 item untuk diuji validitas dan reliabilitas. Validitas isi menggunakan content validity index (CVI) dan validitas konstruk menggunakan principal component analysis (PCA). Alpha Cronbach digunakan untuk menguji reliabilitas instrumen. Hasil uji validitas menunjukan sebanyak 9 item valid dan reliabel, dengan CVI adalah 1 dan nilai Measure of Sampling Adequacy (MSA) kurang dari 0.5, serta nilai Cronbach Alpha adalah  0.682. Dengan demikian, instrumen SIDIK SIAMA telah mencapai validitas dan reliabilitas yang baik, sehingga dapat dipakai untuk mendeteksi risiko stunting sejak kehamilan.